Wave data for shallow and deep water sedimentary basins of Malaysia - Jameel, M.; Islam, A.B.M.; Salman, F.A.; Khaleel, M.; Jumaat, Mohd Zamin (Advanced Science Letters, 2012)
The recent years have seen significant development of offshore structures in Malaysian region for oil and gas exploration. Analyzing and studying the behavior of offshore marine structures subjected to environment conditions native to Malaysian seas offshore of Terengganu and Sarawak requires that the sea wave characteristics be properly probed. In addition, the knowledge of wave characteristics is essential for planning, design and construction of new ports coastal protection constructions, harbors and navigational channels. It correspondingly contributes to fisheries activities, navigation, marine habitat management and coastal development and planning. As this kind of research is still young for the case of Malaysian oil and gas exploration cum production activity, research methods are introduced and implemented in the study to catch on the wave characteristics in deep water be existent at offshore Terengganu and Sarawak. These essentially include obtaining reliable sea wave data for the purpose of offshore engineering design, studying the wave height distributions to predict the probability of occurrences of different sea states. Subsequently, the wave data's for the water depths of the Terengganu and Sarawak basin, which is 200 m (shallow) and 2000 m (ultra-deep) respectively are developed. The sea wave data have been predicted for 100 years occurrence probabilities and 1000 years return periods.